Symmetric optical multipass matrix systems and the general rapid design methodology - Xiao, Xiangjun; Shi, Miyun; Qiu, Jingjing; Ou, Xue; Liu, Peng; Zhou, Xin (Heliyon, 2024)
We proposed an original type of multipass cell named symmetric optical multipass matrix system (SMMS), in which the same matrix patterns of various sizes can be formed on both sides. According to its special symmetric configurations, the SMMS design problem is modeled as a variant of the classical traveling salesman problem, which can be rapidly solved by evolutionary optimization algorithms. Two sets of 3-mirror SMMSs are designed, analyzed and built, which show superior characteristics of high stability, desirable beam quality and adjustable optical path lengths. Additionally, they can support simultaneous detection of multiple species with multi-laser channels. The proposed method is further extended to design a 4-mirror SMMS, which verifies the universality and robustness of the design methodology. The experimental observations are in consistent with the theoretical calculations. The newly proposed SMMSs have a broad application prospect in trace gas measurement. •A novel symmetric optical multipass matrix system (SMMS) is proposed.•SMMSs have the advantages of the high stability, desired beam quality, long and adjustable optical path lengths.•SMMSs provide great convenience to design multi-laser channels for simultaneous multi species trace gas sensing.